Hubungan Pengetahuan dan Sikap Ibu tentang Pemeriksaan Inspeksi Visual Asam Asetat di Puskesmas Poasia Kota Kendari - Kartini, Kartini (Poltekkes Kemenkes Kendari, 2017)
Cervical cancer affects a large number of people. Cervical cancer Cervical cancer is actually the second most prevalent cancer affecting women in the globe, while cervical cancer is the first in developed countries. This research aims to assess the connection between the awareness and attitudes of the mother in the Poasia Health Center, City of Kendari, on visual inspection with acetic acid (VIA). ,This is cross-sectional analysis, the sample of research was in PUS, 72 in the Center for Health Poasia, Kendari Region. The data collection method was an information and attitudes questionnaire on the VIA study. Chi-square testing was performed for analysis of results. The results showed that most of PUS' knowledge of the VIA test was in the lack of knowledge group in Puskemas Poasia in Kendari District. The key attitudes of the PUS towards the IVA test were in the negative category at the Poasia Health Centre, in Kendari District. Many reproductive women have ample knowledge of their positive attitudes, while the majority of reproductive-age women have less knowledge of adverse attitudes. In Puskesmas Poasia, City of Kendari, there is a connection between mother's information about vision inspection with acetic acid.